Variability studies in fodder sorghum sorghum bicolor (L.) Moench - Bini K (Department of Plant Breeding and Genetics, College of Agriculture, 2003)
A research programme was carried out in the Department of Plant Breeding and Genetics, College of Agriculture, Vellayani during August to November 2002 with the objective of estimating the variability in important economic characters and to select superior accessions of fodder sorghum .The experiment was conducted using 50 accessions of fodder sorghum collected from ICRISAT adopting a randomized block design with two replications. Data collected on eleven characters were subjected to statistical analysis. Coefficients of variation, heritability, genetic advance, correlation among the characters, path analysis and selection index were estimated. Analysis of variance revealed significant difference among the accessions for all the characters. Phenotypic and genotypic coefficients of variation were high for leaf weight per plant, green fodder yield, number of leaves per plant, leaf area index and number of tillers per plant. High heritability coupled with high genetic advance for plant height at harvest, leaf weight per plant and green fodder yield revealed the presence of additive gene action. Hence simple pedigree method will be effective for improvement of these traits. Correlation studies indicated that crude protein content, leaf weight per plant, plant stand after germination, leaf area index and plant height at harvest exhibited significant positive correlation with green fodder yield. Leaf weight per plant exhibited the highest positive direct effect on green fodder yield followed by leaf area index and plant height at harvest. Based on selection index with respect to eleven characters studied, ten superior accessions were selected by exercising 20 per cent selection. They were Acc. Nos.11079, 11026, 11446, 680, 11456, 670, 11128, 11298, 1005 and 902.